Scary stories to tell in the dark : three books to chill your bones - Schwartz, Alvin, 1927-1992 (Edge books. Scary stories., 2019)
Traditional and modern-day tales and "jump" stories of ghosts, witches, vampires, haunts, superstitions, monsters and horrible scary things.